International teacher education promising pedagogies (part c) - Craig, Cheryl J.; Orland-Barak, Lily. (Bingley, U.K. : Emerald, 2015)
All countries in the world understand that education is vital to human and economic prosperity and that teacher education unavoidably is implicated. But the snag is this: political forces shaping public opinion in individual nations (particularly the U.S.) are deeply divided concerning how teacher education should proceed. This book acknowledges this Achilles heel tension, but does not become weighed down by it. Instead, it focuses on 'the practical' (Schwab, 1969), matters that have been locally deliberated and enacted. Pedagogies are named, origins (cultural/practical/theoretical/policy roots) are traced and a live example of the pedagogy unfurling in the local setting is presented from an insider-view.
Cultivating student teachers' moral competencies in teaching during teacher education / Auli Toom, Jukka Husu, Kirsi Tirri -- The theory-practice divide : the case of Denmark / Per F. Laursen -- Connecting theory and practice in initial teacher training in Italy : the University of Bari experience of the multimodal laboratory / Chiara Gemma, Laura Sara Agrati -- Promoting preservice teachers meta-representational (visual) competencies : the need for a new pedagogy / Billie Eilam -- Multigrade teaching in primary education as a promising pedagogy for teacher education in Austria and Finland / Eeva Kaisa Hyry-Beihammer, Tina Hascher -- Embodiment : a multimodal international teacher education pedagogy? / Rachel Forgasz -- Faith communities and community engagement based teacher education : a pedagogy of promise / Jude Butcher, Anthony Steel -- A programmatic focus on engaging families, communities and children : institutionalizing assets-based pedagogies / Rene<U+0301>e T. Clift ... [et al.] -- Pedagogy of formative assessment : a Mexican exemplar / Alejandra Garci<U+0301>a-Franco, Jose Antonio Chamizo Guerrero -- Preservice teachers reflective portfolio : evaluating teaching and learning in teacher education in China / Zhuo Feng, Xiao Han -- Electronic portfolios as pedagogy : using bportfolios for authentic assessment of teacher knowledge and skills in the US / David Wicks, Andrew Lumpe -- Composing a life as a teacher educator / Sean Lessard ... [et al.] -- Pedagogies for teacher education policy development in Canada : democratic dialogue / De<U+0301>irdre Smith -- The policy analysis and debate on "internship" : an exemplar of research conducted at the center for teacher education research, Beijing Normal University / Xudong Zhu, Li Yuan, Siying Chen -- Israel's MOFET Institute : "community of communities" for the creation and dissemination of knowledge of teacher education / Michal Golan, Rivka Reichenberg -- The use of evidence to improve education and serve the public good : New Zealand's best evidence synthesis programme / Adrienne Alton-Lee -- InFo-TED : bringing policy, research, and practice together around teacher educator development / Eline Vanassche ... [et al.] -- Concluding chapter (part c) / Cheryl J. Craig, Lily Orland-Barak -- Series concluding chapter (parts a, b and c) / Cheryl J. Craig, Lily Orland-Barak.
Print version record
Keywords: Education -- General; Teaching skills & techniques; Teachers -- Training of -- Cross-cultural studies; International education